Effects of Size and Shape on Elastic Constants of Graphene Sheet. (February 2018) - Azimi Resketi, N.; Ahmadie Amiri, H.; Dehestani, M.
Abstract: Nanotechnology is used in different engineering fields such as mechanical, aerospace, and civil. One of the most interesting structures which recently have come to the center of attention is the Graphene Sheet (GS). Graphene is a material with high potential of usage in civil structures like structural rehabilitation. In the present paper a finite element based structural analysis program is employed to study the mechanical properties of GS. The advantage of using this method is its simplicity and efficiency in different types of loading. The models considered here are based on a structural mechanics approach by using finite beam elements. Variations of Young's moduli of GS versus different sizes of sheet in two principal directions are investigated. Afterwards, Poisson's ratio and shear modulus for a special case are obtained. The results are consistent with basic structural mechanics theory. Final results reveal the importance of GS size on its Young's modulus, Poisson's ratio and shear modulus. The results are in good agreement with previously published results by other scientists.